Security in Iraq A Framework for Analyzing Emerging Threats as U.S. Forces Leave - Gompert, David C. (RAND Corporation, 2010)
U.S. withdrawal could affect Iraq's internal security and stability, which could, in turn, affect U.S. strategic interests and the safety of U.S. troops and civilians in Iraq. U.S. policy-makers need a dynamic analytic framework with which to examine the shifting motivations and capabilities of the actors that affect Iraq's security. Within this framework, the United States should be able to contribute to continued strengthening of the internal security and stability of Iraq even as it withdraws its forces.